A Sequential Three-Phase Pathway Constitutes Tracheary Element Connection in the Arabidopsis/Nicotiana Interfamilial Grafts - Deng, Zhuying; Wu, Huiyan; Jin, Tianlin; Cai, Tingting; Jiang, Mengting; Wang, Mi; Liang, Dacheng (Frontiers in Plant Science, 2021)
Scion–rootstock union formation is a critical step towards functional assemblage of heterogeneous plants. Interfamilial scion-rootstock interaction often results in graft incompatibility during the assemblage process and the underlying mechanisms are largely unknown. In this study, we reported that tracheary element (TE) remodeling including TE segmentation and deformation, rather than de novo formation from callus or adjacent tissues, took place at the early stage of grafting interface between Arabidopsis thaliana and Nicotiana benthamiana (At/Nb). Following cellular deposits, the short TEs from both partners were overlapping, dependent of the homogeneity of contacting TEs, with each other. Without overlapping, the TEs at the interface would grow laterally and the TEs above and below the interface would undergo self-fusion to form insulating spiraling bundles. Finally, the overlapping TEs constituted a continuous network through alignment. Our results provide a definitive framework for the critical process of TE behavior in the At/Nb distant grafts, including: (1) segmentation and/or deformation, (2) matching, overlapping and cellular deposits, (3) aligning or spiraling. These insights might guide us in the future in constructing more compatible distant grafts from the perspective of TE homogeneity.